Juridical Study of the Constitutional Court's Decision No. 22/PUU-XV/2017 Regarding Restriction of Marriage Age in the Perspective of Maslahah Theory by Muhammad Saʻîd Ramaḏân Al-Bȗṯî’s and Gender Equality in Islam - Syifa’, Machrus Ali; Kharlie, Ahmad Tholabi; Sahid, Mualimin Mochammad (Universitas Islam Negeri Raden Intan Lampung, 2020)
This article is intended to answer questions on the legal considerations of the Constitutional Court Decision No. 22/PUU-XV/2017 regarding the minimum age of marriage for women and how the Judgment is seen from the Muhammad Saʻîd Ramaḏân al-Bûṯî's maslahah theory and the theory of gender equality in Islam. From the conducted studies, several conclusions can be drawn. First, the Judge's legal considerations in canceling the minimum age of marriage in decision No. 22/PUU-XV/2017 are based on consideration of discrimination acts, health and educational aspects, child exploitation, the minimum age requirement for marriage in various countries, and policy demands related to marriage age. Second, in terms of the al-Bûṯî’s maslaẖah theory, the Constitutional Court's ruling on the equalization of marital age between men and women is not categorized as a maslahah, since it does not meet the five criteria for something to be called as a maslahah. Third, according to the gender equality theory in Islam, it can be concluded that the Constitutional Court's decision is not suitable to the theory, since the meaning of equality in Islam is not to be equal but rather to the fulfillment of rights according to the level of needs.